Hydrogen Production and Purification by Bioethanol Steam Reforming and Preferential Oxidation of CO - Arévalo, Juan David; Martinez Hernández, Ángel; Vargas, Julio César; Córdoba, Luis Fernando (TECCIENCIA, 2018)
Hydrogen production and purification was studied in a combined system including double catalytic bed reaction system. Steam Reforming of Ethanol (SRE) was performed in Ni/CeO2-ZrO2 catalyst and, subsequently, the reforming products gases passed through a second fixed bed containing Au/CeO2-ZrO2 catalyst in order to carry out the preferential CO oxidation (PROX-CO). Initially, the effect of temperature and the initial water concentration in the fed ethanol were evaluated to determine the conditions that maximize the H2/CO ratio while maintaining 100% conversion of ethanol. These requirements were accomplished when 25 mole% H2O and 4 mole% C2H5OH (steam/ethanol molar ratio = 7) were used. The catalyst stability was assessed under these reaction conditions at 600°C, during more than 160 h on stream, obtaining ethanol conversions above 99% during the entire test and H2 productivity close to ideal. In the second part of the work, in order to obtain H2 grade PEM, the effect of O2 concentration in the feed stream on the selective CO oxidation using Au-CZ catalysts was investigated in the temperature range of 50-250°C. Catalytic stability test was also performed. Characterization techniques: Temperature Programmed Reduction (TPR), X-Ray Diffraction (XRD), SEM-EDX, which confirmed the presence of a strong interaction between the mixed oxide support and the metal. In this study, we show a reaction system with double catalytic fixed bed in which hydrogen is obtained with the specifications required by PEM fuel cell. The tested materials exhibit high activity and selectivity towards hydrogen production and CO selective oxidation in the range of temperature studied.